Ecological strategies of Hyphantria cunea (Lepidoptera: Arctiidae) response to different larval densities - Zhao, XuDong; Geng, YiShu; Hu, TianYi; Xie, ChuXia; Xu, WenXuan; Zuo, Zhuang; Xue, MingYu; Hao, DeJun (Frontiers in Ecology and Evolution, 2023)
Population density is an essential factor affecting the life history traits of insects and their trade-off relationships, as increasing density intensifies intraspecific competition. It decreases the average resources available to individuals within a population, affecting their morphology, physiology, behavior, and fitness. The fall webworm, Hyphantria cunea (Drury) (Lepidoptera: Arctiidae), has been an invasive pest of forest trees, ornamental plants, and fruit trees in China for many years. The larvae have a typical aggregation habit before the fourth instar and keep spitting silk to gather the damaged leaves into silk webs. This study investigated the critical biological parameters, food utilization, and population parameters of H. cunea in response to different rearing densities. We found that a high larval rearing density significantly reduced pupal mass and female fecundity, and larvae developed rapidly and had a higher survival rate under crowding conditions. In lower-rearing density, we found that the developmental period of H. cunea larvae was prolonged, and mortality was increased. Nevertheless, higher food utilization, greater body size, and higher female fecundity were observed. Both males and females had similar development strategies in response to the density factor. However, females seemed to be more resistant to crowding than males. Moreover, no significant differences in R0, r, and λ were observed across population densities. On the other hand, the mean generation time (T) of H. cunea populations raised in low density is longer than that of populations raised in groups. In conclusion, H. cunea could adopt different ecological strategies for density factors. High population densities result in shorter generation cycles and higher survival rates. Conversely, the low-density generation period becomes longer but with greater fecundity. The results may help determine the possible outbreak mechanism and develop effective population monitoring and forecasting measures of H. cunea.